2022
DOI: 10.3390/plants11202776
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic CuO and ZnO Nanoparticles as Nanofertilizers for Sustainable Growth of Amaranthus hybridus

Abstract: The biogenic synthesis of CuO and ZnO nanoparticles (NPs) was carried out by Stenotrophomonas maltophilia. The shape, size, and chemical identity of the CuO and ZnO NPs were determined using FTIR, XRD, SEM, EDX, and TEM analysis. The study aimed to investigate the effects of the CuO and ZnO NPs on Amaranthus hybridus seed germination and plant growth. Two different fertilizer application modes (hydroponics and foliar) were studied with varying concentrations of CuO (0.06 µM, 0.12 µM) and ZnO (0.12 µM, 0.24 µM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 91 publications
1
14
0
Order By: Relevance
“…The results demonstrated the negative impact of CuO nanoparticles on seed germination, with a decrease of 71.33% for the control group to as low as 5.7% with increased CuO concentrations. 164 Ndaba et al 165 examine the impact of iron oxide nanoparticles synthesized from an extract of African mugwort (Artemisia afra) leaves on the germination of spinach. The nanoparticles were tested at different concentrations (5, 10, 30, 50, 100, and 150 ppm) and significantly improved the length of spinach and carrot roots and shoots, with the best results obtained at the lowest concentration (5 ppm) Fig.…”
Section: Seed Primingmentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrated the negative impact of CuO nanoparticles on seed germination, with a decrease of 71.33% for the control group to as low as 5.7% with increased CuO concentrations. 164 Ndaba et al 165 examine the impact of iron oxide nanoparticles synthesized from an extract of African mugwort (Artemisia afra) leaves on the germination of spinach. The nanoparticles were tested at different concentrations (5, 10, 30, 50, 100, and 150 ppm) and significantly improved the length of spinach and carrot roots and shoots, with the best results obtained at the lowest concentration (5 ppm) Fig.…”
Section: Seed Primingmentioning
confidence: 99%
“…The results demonstrated the negative impact of CuO nanoparticles on seed germination, with a decrease of 71.33% for the control group to as low as 5.7% with increased CuO concentrations. 164…”
Section: Agriculture and Nano-fertilizersmentioning
confidence: 99%
“…The peaks around 3450 cm −1 have been attributed to the stretching vibrations of amide I superimposed on the side of the hydroxyl group band, which supports the existence of the proteins and, consequently, the biosynthesis of WO 3 , CuO, and ZnO nanoparticles. SEM analysis revealed that the morphology of CuO, ZnO, and WO 3 nanoparticles was spherical and less than 100 nm ( Figure S3a–c ) [ 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…ZnO NPs could be an innovative nanofertilizer to add Zn to the required soil . According to Francis et al, ZnO NPs on plants at 0.12 and 0.24 M exhibit significant antioxidant concentrations, ensuring better plant protection from diseases and pests and boosting plant growth . To improve plant and Zn nutrient growth for agricultural sustainability, Itroutwar et al synthesized biogenic ZnO NPs as an efficient nanopriming agent for seed treatment …”
Section: Introductionmentioning
confidence: 99%
“…26 According to Francis et al, ZnO NPs on plants at 0.12 and 0.24 M exhibit significant antioxidant concentrations, ensuring better plant protection from diseases and pests and boosting plant growth. 27 To improve plant and Zn nutrient growth for agricultural sustainability, Itroutwar et al synthesized biogenic ZnO NPs as an efficient nanopriming agent for seed treatment. 28 Generally, the seed goes through many metabolic changes throughout the germination period.…”
Section: ■ Introductionmentioning
confidence: 99%